Penyelesaian Utang Melalui Rencana Perdamaian: Analisis Kasus PKPU PT Adhi Persada Properti - Muhammad Afuza Fauzan Adhim; Puspita Anggi Kurnianita; Putri Cahyani; Emma Yunika Puspasari (Pemuliaan Keadilan, 2025)
This study examines the debt restructuring process of PT Adhi Persada Properti through a Penundaan Kewajiban Pembayaran Utang (PKPU) proceeding. By employing a normative legal research method with a descriptive approach, this study analyzes the legal framework governing PKPU and its application in the case of PT Adhi Persada Properti. The findings reveal that the company's delay in submitting a peace plan and the lack of a clear restructuring strategy have raised concerns about the fairness of the process for creditors. The study highlights the importance of timely compliance with legal requirements in PKPU proceedings and the need for a balanced approach that protects the interests of both debtors and creditors.